THE ESSENCE AND PECULIARITIES OF THE ELECTRIC POWER INDUSTRY AS AN OBJECT OF ADMINISTRATIVE AND LEGAL INFLUENCE (Bulletin of criminological association of Ukraine, 2023)
The article emphasizes that the electric power industry as an object of administrative and legal influence is considered in the domestic administrative and legal doctrine through the prism of electronic governance. It was determined that the essence of the electric power industry as an object of administrative and legal influence is reduced to social relations of storage, aggregation, transmission, distribution, purchase and sale, transfer, use, measurement and savings, including in the framework of international cooperation, electricity, as well as solving a number of problems in the field of public administration, related to the formation of a culture of energy saving among public servants and the entire population of Ukraine, the development of energy management, energy efficiency and environmental friendliness in the domestic electric power industry. It is noted that in view of the proposed understanding of the essence of the electric power industry as an object of administrative and legal influence, it is appropriate to start the consideration of the relevant features of the latter with the close interdependence of the domestic electric power industry with the formation of the culture of energy conservation among the population. The phenomenon of culture is extremely multifaceted, embodied at the level of administrative and legal doctrine in traditional culture, corporate culture and the culture of administrative values. It is emphasized that another feature of the electric power industry as an object of administrative and legal influence is adaptability and openness to innovations, which are manifested both at the level of behavior of electricity consumers and at the level of public management in the field of electric power. Under administrative innovations in the context of the study, not only changes in rules and structures are defined, but also a complex, multifaceted, essential rethinking based on domestic and foreign doctrine, the experience of the world's leading states of tasks and functions, subject matter and boundaries, a system of subjects, administrative tools and other important aspects of public management in the field of electricity. Other features of the electric power industry as an object of administrative and legal influence include the need to measure, model and forecast electricity consumption and the fact that energy management is the organizational and management basis of administrative and legal influence.
Keywords: electric power industry; object of administrative and legal influence; essence; features; electronic governance; culture of energy saving; energy management